Peranan Asas-Asas Hukum Perjanjian Dalam Mewujudkan Tujuan Perjanjian Bisnis - Ardiansyah , Adam; Nurjaman , Ari; Saputra , Arzil Azizah Saputra; Febriansyah , Dandi; Rafles, Fadhlu Rohman Dian (Universitas Dehasen Bengkulu, 2024)
Article 1313 of the Civil Code states that an agreement is an act in which one or more people bind themselves to one or more other people. In general, the agreement is the agreement of the parties about a matter that creates a legal relationship, raises the rights and obligations and if not executed as promised it will impose sanctions. The purpose of the agreement is to be the basis of a settlement if problems arise later in order to protect the parties, obtain legal certainty and justice. This study discusses the things that must be considered or fulfilled in making agreements and how the role of the principles of a legal agreement in realizing the objectives of the agreement. The settlement of the dispute of the agreement shall be settled not solely on the basis of what is written in the agreement but to consider the harmony of all the principles of the law of the agreement, namely the principle of contractual freedom, the principles of consensualism, the principles of legal certainty (pacta sunt servanda), good faith principles, personality principles, trust principles, principles of equality of rights, moral principles, The principle of propriety, customary principle, equilibrium principles, and The principle of protection.